Study of Rod-Plate DC Discharge Plasma Characteristics at Atmospheric-Pressure - Kadhim, Murad M.; Khalaf , Thamir H.; Abbas, Qusay A. (Iraqi Journal of Science, 2022)
The characteristics of atmospheric-pressure glow discharge (APGD) produced by rod-plate electrodes are experimentally determined. APGD is sustained by applying a high DC voltage between the electrodes. At atmospheric pressure, the shift from corona discharge to glow discharge is investigated. A rod-plate discharges configuration’s volt–ampere properties show the existence of three discharge regimes: corona, glow, and spark. The variations in the electrical field distribution in the various regimes are mirrored in the discharge luminosity. The rod-plate patterns are created under a dark region, and are visible mainly due to the effect of electrons heated by the local enhanced electric field at the interface, according to the optical emission spectra of the entire discharge.